Integrating spiritual wisdom into occupational health practice: Insights from the Bhagavad Gita - Khagendra Neupane, (International Journal of Occupational Safety and Health, 2026)
This paper explores how the teachings of Bhagavad Gita contribute to enhance  occupational health and safety of the employees in the workplace. Modern occupational health and safety (OHS) practices have become effective in addressing physical and psychosocial risks. However, they fail to deal with emotional challenges faced by employees Hence, the spiritual approaches have drawn the attention of both employer and employees to enrich workplace resilience and integrity. This study answers how the spiritual teachings of the Bhagavad Gita contribute to promoting holistic approaches for the safety of employees and their ethical culture. The research seeks to integrate core Gita’s teachings into modern OHS frameworks with a view to enhancing emotional resilience and ethical behavior of employees.  The teachings such dharma (righteous duty), vairāgya (detachment), abhyāsa (practice), ātma-jñāna (self-knowledge), and sthita-prajña (emotional stability) offer deep insights in order to foster mental health, ethical conduct and purposeful action in high-pressure occupational settings. The study develops a psychospiritual model for occupational health and safety. The study draws its reference from Eknath Easwaran’s translation of the Gita. It also focuses recent research in positive organizational psychology, mindfulness-based stress reduction and psychosocial risk frameworks. This interdisciplinary study illustrates how ancient wisdom can complement modern practices. The proposed model emphasizes inner transformation as a foundation for external well-being. It offers a holistic approach to OHS that includes ethical clarity, emotional regulation, resilience and self-transcendence. Ultimately, this article argues that the Bhagavad Gita, acting as a practical manual for cultivating occupational health in the modern era, makes a paradigm shift toward psychospiritual integration in workplace policies, training and leadership development.